Training load and acute performance decrements following different training sessions - Vermeire, K. M.; Caen, K.; Bourgois, J. G.; Boone, J. (International Journal of Sports Physiology and Performance, 2023)
Purpose: To examine the differences in training load (TL) metrics when quantifying training sessions differing in intensity and duration. The relationship between the TL metrics and the acute performance decrement measured immediately after the sessions was also assessed.